Highly Textured BaTiO3 via Templated Grain Growth and Resulting Polarization Reversal Dynamics. Issue 3 (13th December 2015) - Meier, William; Meyer, Kelsey Elizabeth; Sava Gallis, Dorina F.; Blea‐Kirby, Mia Angelica; Roth, Joshua; Felman, Daniel; Breuer, Tim; Dension, Gary J.; Zutavern, Fred J.; Huebner, Wayne; Brennecka, Geoff L.
Abstract : Samples of bulk textured polycrystalline BaTiO3 ceramics were fabricated using a templated grain growth (TGG) approach in order to investigate effects of polycrystallinity and texture related to ferroelectric domain reversal under high‐power drive conditions. Barium titanate platelets were formed via two‐step topochemical conversion of bismuth titanate platelets grown via molten salt synthesis, then aligned via tape casting within a matrix of fine BaTiO3 powder. The coarse‐grained parts showed a high degree of crystallographic texture after sintering. Combined with ceramics of similar density and polycrystallinity, but random orientation and commercial single‐crystal specimens, this sample set enabled direct isolation of crystallographic texture and polycrystallinity as the primary variables for high‐power polarization reversal studies. These studies have also demonstrated a link between grain size and polarization reversal time that strongly suggests that grain boundaries serve effectively as nucleation sites during the ferroelectric switching process.